Fate of Listeria monocytogenes Inoculated onto Turkey Ham and Treated with Sodium Metasilicate - Sharma, C.S.; Williams, S.K.; Rodrick, G.E. (International Journal of Poultry Science, 2012)
Sodium Metasilicate (SMS) is a USDA approved antimicrobial and has been shown to be inhibitory towards various foodborne pathogens in refrigerated raw poultry and beef trimmings. The objectives of this study were to determine the antimicrobial effects of SMS against Listeria monocytogenes in ready-to-eat turkey ham and to ascertain effects of various treatments on pH. Ready-to-eat turkey ham slices were inoculated with L. monocytogenes, treated with either 0% SMS (only sterile de-ionized water) and no inoculum (negative control), 0% SMS (only sterile de-ionized water) and inoculum (positive control) and 6% SMS solution with final concentration of 300 ppm and 600 ppm of SMS in turkey ham samples plus inoculum. In each treatment, the turkey ham samples were vacuum-packaged and stored at 4±1°C. All samples were analyzed on day 0, 7, 14, 21 and 28 of storage for presence of L. monocytogenes and pH. The use of 6% SMS solution at 300 and 600 ppm concentrations was not effective in reducing L. monocytogenes populations (p>0.05) in turkey ham and pH values were similar (p>0.05) for all treatments from d 0 to d 28. The findings from this study suggested that SMS is ineffective in reducing L. monocytogenes in turkey ham, at the currently approved levels and higher concentrations of SMS may be needed to restrict growth of L. monocytogenes in ready-to-eat poultry products.